Quantitative genetic traits of eight grassland species from three regions of Germany (Schwäbische Alb, Hainich-Dün, Schorfheide Chorin) - Völler, Eva; Bossdorf, Oliver; Prati, Daniel; Auge, Harald (Supplement to: Völler, E et al. (2017): Evolutionary responses to land use in eight common grassland plants. Journal of Ecology, https://doi.org/10.1111/1365-2745.12746, 2017)
This study was carried out within the Biodiversity Exploratories (www.biodiversity-exploratories.de), a large-scale and long-term project for investigating relationships between land use, biodiversity and ecosystem processes (Fischer et al. 2010, doi: 10.1016/j.baae.2010.07.009). The core of this project is a network of standardized field plots in grasslands and forests in three different regions of Germany - Schwäbische Alb, Hainich-Dün and Schorfheide-Chorin. Within each region, there are 50 grassland plots covering a wide range of land-use types and intensities. The aim of our study was to test how differences in land use generate genetic differences among populations across multiple regions and grassland species, and thus to assess how common and how consistent evolutionary responses to land use are in grassland plants, which land-use factors contribute most to genetic differentiation, and which plant traits are most responsive. We studied eight grassland species that occurred in all three regions and all land-use types, with 23 to 108 populations per species. In the summer of 2008, we visited all 150 grassland plots in the three regions three times (in June, July, August) and collected mature seeds in all plots where the species occured. We germinated the seeds of all maternal families of all species and transplanted one seedling from each of 10 maternal families per population and species separately into pots in a common garden. During plant growth we measured several traits. We recorded flowering phenology, defined as the time when the stamina were visible on grasses and when the first flower opened on herbs. We harvested plant aboveground biomass at the time of seed maturity. For each plant, we also determined the maximum plant height as the length of the longest tiller or stem, and we counted the total number of inflorescences or flowers. We then separated aboveground biomass into vegetative parts (tillers or stems) and reproductive parts (inflorescences or flowers), dried all biomass samples and weighed them. We calculated total aboveground biomass as the sum of vegetative and reproductive mass, and reproductive allocation as the ratio between reproductive and total aboveground biomass.